Growth and Yield of Various Soy Varieties (Glycine max L. Merr.) on Drought Stress - Rusmana, Rusmana; Ningsih, Eltis Panca; Justika, Amelia (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2020)
Soybeans become a source of plant protein and an essensial food ingredient in Indonesia. Extreme climate change causes weather changes; the impact is a long dry season which results in drought. Efforts to deal with drought stress are carried out using drought-tolerant soybean varieties that drop of production can be suppressed. The purpose of the study is to study growth responses for several different soybean varieties with drought-stricken conditions. The research was conducted from October 2019 to January 2020 at the Green House Agroecotechnology Laboratory of the Faculty of Agriculture, University of Sultan Ageng Tirtayasa, Banten. Factorial randomized block design method was then used which consists of two factors and three repetition. The first factor were that the Varieties consists of V1: Argo mulyo variety; V2: Deja 2 and V3 varieties: Dena varieties. The second factor was drought percentage comprising k1: 100% ATT (Groundwater Available); k2: 80% ATT, k3: 60% ATT and k4: 40% ATT. The results showed that differences in varieties and drought stress did not significantly affect the growth and yield of soybean crops. Argo Mulyo varieties are superior to drought stress compared to Deja 2 and Dena varieties from the weight of 100 seeds. No interaction of different soybeans varieties treatment and drought stress on all observation parameters.